A DSGE Decision Model for Investigating the LPR Transmission Effect. (21st January 2022) - Yang, Xing
Abstract : In August 2019, People's Bank of China launched the reform of Loan Prime Rate (LPR) quotation formation mechanism and then made continuous progress in the order of "new loans first, followed by exiting loans, " dredging the interest rate transmission channel of "policy interest rate, LPR, loan interest rate." In 2020, Chinese financial institutions have mainly referred to LPR pricing for loans, and the marketization level of loan pricing has significantly improved. This paper analyzed the policy effects transmitted by LPR through constructing a Dynamic Stochastic General Equilibrium (DSGE) decision model, and it was found that the financial market structure, pricing ability of commercial banks, and the degree of LPR application all affected the policy rate transmission effect and had an impulse impact on macroeconomic growth. Based on the above analysis, this paper proposed policy suggestions on the path of interest rate market-oriented reform and coping measures of commercial banks in China.